HEREDITARY DISTAL FORELEG CURVATURE IN THE RABBIT : I. MANIFESTATIONS AND COURSE OF THE BOWING DEFORMITY: GENETIC STUDIES - Pearce, Louise (The Rockefeller University Press, 1960)
An inwardly directed curvature of the distal segment of both forelegs of the rabbit has been described. The condition was detected at 2 to 3 weeks of age, developed rapidly, and reached its final and permanent stage at 2 to 3 months of age. Only the distal epiphysis of the ulna was primarily affected and this in the form of a massive chondrodystrophic lesion accompanied by a progressive curvature of the shaft. The curvature of the growing radius was a secondary effect due to the firm, immovable, anatomical connection of the ulna and radius. The positional changes of the wrist and paw were likewise effects secondary to the changed form of the ulna and radius. The bowing abnormality occurred only in certain families of pure bred Beveren, Belgian, French Silver, and Dutch rabbits and was found to be inherited. The mode of inheritance was on the basis of a single recessive unit factor (5).